Assessment of Herbal Medicament in Treatment of Oral Lichen Planus Lesion - Ravinder Singh; Cheena Singh; Nidhi Aggarwal; Sushruth Nayak; Prachi Nayak; Veenu Dahiya; K Saidath (Journal of Pharmacy and Bioallied Sciences)
Objectives: Comparative assessment of effectiveness of topical coconut cream, pomegranate, and Tacrolimus 0.1% in treatment of oral lichen planus (OLP) lesion. Materials and Methods: Thirty patients with histologically confirmed symptomatic OLP exhibiting gingival manifestation were included in this investigation. Group A received topical coconut cream, Group B received pomegranate, and Group C received topical tacrolimus 0.1% ointment. The participants were split into these three groups. For six months, the participants were told to use topical medicines twice a day. For the purpose of monitoring any relapse, the patients were summoned back one, three, and six months after the therapy was stopped. Result: Both the extent of the lesion and the burning sensation/pain were significantly reduced in all groups of participants. Conclusion: The size of the lesion and the burning feeling were significantly reduced when using coconut cream. For the treatment of OLP, tacrolimus, coconut cream, and pomegranates are viable topical pharmaceutical alternatives.